Age-related changes in the local milieu of inflamed tissues cause aberrant neutrophil trafficking and subsequent remote organ damage - Barkaway, Anna; Rolas, Loïc; Joulia, Régis; Bodkin, Jennifer; Lenn, Tchern; Owen-Woods, Charlotte; Reglero-Real, Natalia; Stein, Monja; Vázquez-Martínez, Laura; Girbl, Tamara; Poston, Robin N.; Golding, Matthew; et al. (Immunity, 2021)
Aging is associated with dysregulated immune functions. Here, we investigated the impact of age on neutrophil diapedesis. Using confocal intravital microscopy, we found that in aged mice, neutrophils adhered to vascular endothelium in inflamed tissues but exhibited a high frequency of reverse transendothelial migration (rTEM). This retrograde breaching of the endothelium by neutrophils was governed by enhanced production of the chemokine CXCL1 from mast cells that localized at endothelial cell (EC) junctions. Increased EC expression of the atypical chemokine receptor 1 (ACKR1) supported this pro-inflammatory milieu in aged venules. Accumulation of CXCL1 caused desensitization of the chemokine receptor CXCR2 on neutrophils and loss of neutrophil directional motility within EC junctions. Fluorescent tracking revealed that in aged mice, neutrophils undergoing rTEM re-entered the circulation and disseminated to the lungs where they caused vascular leakage. Thus, neutrophils stemming from a local inflammatory site contribute to remote organ damage, with implication to the dysregulated systemic inflammation associated with aging.
CRIS-Team Scopus Importer:2021-07-16
Keywords: ACKR1; aging; chemokines; CXCR2; diapedesis; endothelium; extravasation; inflammation; mast cells; Neutrophils